Variations of external load variables between medium- and large-sided soccer games in professional players - Clemente, F. M.; Sarmento, H.; Rabbani, A.; Van Der Linden, C. M. I.; Kargarfard, M.; Costa, I. T. (Research in Sports Medicine, 2019)
This study compared the relative physical demands of official matches and sided games (medium and large) in professional soccer players by means of a global positioning system. Twenty-three professional male soccer players (24.632.84 years old; 180.946.49 cm; 77.196.46 kg; 52.995.01 VO2max) participated in the study. Total distance, running distance, sprinting distance, number of sprints, and acceleration sum were quantified per minute to compare the different games. Running distance in full match was greater than in 5vs5+GK (d = 2.303, moderate effect), 6vs6+GK (d = 1.719, moderate effect) and 9vs9+GK (d = 1.084, minimum effect) sided games. Greater values for sprinting distance were found in the full match compared to 5vs5+GK (d = 3.673, strong effect), 6vs6+GK (d = 2.606, moderate effect) and 9vs9+GK (d = 1.903, moderate effect) sided games. However, the load was greater in the 5vs5+GK game compared to the 6vs6+GK (d = 1.323, moderate effect) and 9vs9+GK (d = 1.030, minimum effect) games and the full match (d = 1.478, moderate effect). This study revealed that medium-sided games are not appropriate for simulating the sprinting conditions of official full matches. However, medium-sided games are more intense than full matches in that accelerations are made more often in medium-sided games.